2020
DOI: 10.1111/are.14791
|View full text |Cite
|
Sign up to set email alerts
|

In vitro screening for the antifungal activity of some Egyptian plant extracts against the fish pathogen Saprolegnia parasitica

Abstract: In the aquaculture industry, fungal infections became important problem in fresh and brackish water fish farms and hatcheries, they are responsible for severe mortalities and worldwide economic losses of cultured and wild fish species (Bangyeekhun, Quiniou,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…However, use of some of these chemicals is either limited or banned due to several undesirable effects such as toxic and carcinogenic properties (Bly et al., 1996), causing the egg's cell wall to be vulnerable to entrance of other pathogens (Branson, 2002; Kirsty et al., 2014; Oono et al., 2008), and the adverse consequences of the repetitive and in high‐dose application on the environment (Bailey, 1984; Bailey & Jeffrey, 1989; Dentler, 1982; Marking et al., 1994; Schreck et al., 1991). Moreover, it has been found that some chemicals that have the competence to effectively eliminate or control the fungus such as permanganate (Sherif & Abdel‐Hakim, 2016), chlorine dioxide, chitosan and copper fibre (Emara et al., 2020) have negative effects on the survival rate of the eggs or juveniles (Good et al., 2020). Therefore, natural therapeutic agents (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, use of some of these chemicals is either limited or banned due to several undesirable effects such as toxic and carcinogenic properties (Bly et al., 1996), causing the egg's cell wall to be vulnerable to entrance of other pathogens (Branson, 2002; Kirsty et al., 2014; Oono et al., 2008), and the adverse consequences of the repetitive and in high‐dose application on the environment (Bailey, 1984; Bailey & Jeffrey, 1989; Dentler, 1982; Marking et al., 1994; Schreck et al., 1991). Moreover, it has been found that some chemicals that have the competence to effectively eliminate or control the fungus such as permanganate (Sherif & Abdel‐Hakim, 2016), chlorine dioxide, chitosan and copper fibre (Emara et al., 2020) have negative effects on the survival rate of the eggs or juveniles (Good et al., 2020). Therefore, natural therapeutic agents (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Eugenol and eugenol acetate were concluded as the most effective antimycotic constituents of S. aromaticum extract (Hussein et al, 2000;Hu et al, 2013), while phenolic compounds as gallic acid, hydroxymethylfurfural and pyrogallol were identified as bioactive compounds in P. granatum extract (Li & Liu, 2015). Recent approaches suggested that the functional plant extract involved antimycotic compounds, which were able to denature proteins of fungal cell wall destroying their selective permeability and blocking vital fungal enzymes, resulting in suppressing essential biochemical pathways of the fungal cell causing cell death (Emara et al, 2020;Gonelimali et al, 2018). Acute fish toxicity of the potential plant extracts revealed that both P. granatum and S. aromaticum exhibited low toxicity to experimental fish recording LC 50 ranged from 1600 to 1330 ppm, and no mortalities were recorded at 400 ppm.…”
Section: Ta B L E 6 Phytochemical Constituentsmentioning
confidence: 99%
“…For example; Tural et al (2019) reported inhibition of aquatic moulds by Thymus vulgaris , Eucalyptus globules and other plant extracts; Pathirana et al (2019) evaluated antimicrobial activity of clove essential oil on fish disease incidence; Khorsavi et al (2012) studied antifungal activities Zataria multiflora and Eucalyptus camaldolensis ; Panase et al (2012) investigated the antimycotic activity of Mangosteen; Caruana et al (2012) evaluated antifungal potential of Atractylodes macrocephala ; Zingiber officinale and Yucca; Hu et al (2013) investigated some of the Chinese medicinal plants and Singh et al (2013) also studied other Indian medicinal plants. Emara et al (2020) investigated antifungal activities of Egyptian medicinal plant extracts on S . parasitica , and they recorded their minimum inhibitory concentration of values ranging from 500 to 125 µg/ml respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saprolegniasis is responsible for significant economic losses in hatcheries and freshwater fish farms across the globe. Saprolegniasis usually appears either as a primary pathogen or as a secondary infection to viral, bacterial, and parasitic agents [10].…”
Section: Introductionmentioning
confidence: 99%